The Impact of covid-19 on occupational therapy students in mental health practice learning placements - Cassim, Feroza (Adolescent Health Research Institute, 2024)
Introduction: Practice learning (PL) is a core feature of occupational therapy (OT) students' curriculum and professional development during their undergraduate training. It promotes students' clinical reasoning abilities and enhances their reflective skills as emerging clinicians, enabling them to graduate as competent healthcare practitioners. However, the covid-19 pandemic interrupted curriculum delivery and forced blended teaching and learning methods. Globally this was recognized to have a significant impact on the training of undergraduate health science students who relied on face-to-face teaching and learning methods. This study aimed to explore the opportunities and barriers that influenced undergraduate OT students' learning experiences within mental health (MH) PL placements during the covid-19 pandemic. Methods: A qualitative descriptive research design was utilized to explore the barriers and opportunities occupational therapy students faced during the covid-19 pandemic in MH PL. Eight undergraduate students were purposively sampled, each participating in a 60-minute individual face-to-face interview which was transcribed verbatim and analyzed inductively using thematic analysis. Findings: Three key themes emerged from the study: 1) Acknowledging ME in the pandemic, describing the need for acknowledgement of what the participants were experiencing during the pandemic, 2) Setup for failure, describing the elements that participants identified as barriers to their ability to thrive in PL and 3) Stuck between a rock and a hard pandemic, demonstrating the opportunities and the barriers for learning which were present in PL placements, and which became more distinct because of the pandemic. Discussion: Complexities of PL in MH PL placements within higher education highlighted the opportunities and barriers which were present in participants' learning experiences, shaping their development as emerging healthcare practitioners. The complexities highlighted the need for additional emotional support structures in the PL learning experience. Social identity constructs, such as language, gender, and culture emerged as critical elements in the consideration of curriculum transformation work impacting PL in South Africa (SA). The context of the pandemic created space for considering how professional identity development is formed and impacted in undergraduate OT students who emerged from the pandemic. Barriers which were present because of the pandemic included feeling underprepared by the pandemic curriculum for PL. Whilst opportunities for learning were positively influenced by peer learning from fellow students. Recommendations included further development of the practice education curriculum in the current PL placements drawing on lessons learnt from the pandemic. Suggested future research is recommended to deepen the understanding on the long-lasting effects of the pandemic on emerging health professionals in a longitudinal study.